Learning And Applying The SHL 3482 (Literature In ELT) By UTM’s TESL Trainees - Abd. Majid , Norazman; Muzaffar Shah, Noor Ashikin (2010)
Teachers of English especially teacher trainees need to be equipped with sufficient knowledge and skills to teach literature in school. The subject of Literature in ELT was taught to UTM’s teacher trainees before they go for teaching practice in order to provide them with adequate skills and knowledge of literature teaching. Thus, this study was carried out to investigate the content of Literature in ELT that have been taught to teacher trainees and to identify the benefits of the subject to teacher trainees. Besides that, this study was also conducted to identify the problems faced by teacher trainees in teaching literature during their teaching practice and to suggest the ways to overcome the problems. 31 third year students of Bachelor Science and Education (TESL) were selected as the respondents of this study. A set of questionnaire was designed to collect the data from the respondents. The overall findings of the study indicate that Literature in ELT do benefits the teacher trainees in preparing themselves to teach literature as most of the respondents rarely face problems in their literature lesson. In conclusion, some suggestions have been made in order to improve the subject of Literature in ELT and recommendations for future research have also been included in the final part of the report.